2018
DOI: 10.1002/rrq.215
|View full text |Cite
|
Sign up to set email alerts
|

Pointing With a Pen: The Role of Gesture in Early Childhood Writing

Abstract: This study explored the connection between gesture and writing in early childhood. Participants were 139 children ages 2 years 6 months to 5 years 11 months attending two U.S. childcare centers serving low‐income, urban families. Qualitative methods were used to record adult–child writing interactions in classroom composing events and in a standard photo caption writing task. Analysis of children's photo captions showed that 55% of children ages 2 years 6 months to 3 years 5 months used at least one kind of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Recent research conducted from this perspective (Rowe, 2019) has shown that children's emergent writing performances provide opportunities for adults to notice, examine, and reframe the child's unconventional marks as if they are symbolic representations of linguistic messages. Questions directed at children texts such as “What does that say?” or “Read that to me!” are not neutral requests for information, but instead frame the child's text as writing and position the child as a writer (Rowe, 2008b).…”
Section: Theoretical Framementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research conducted from this perspective (Rowe, 2019) has shown that children's emergent writing performances provide opportunities for adults to notice, examine, and reframe the child's unconventional marks as if they are symbolic representations of linguistic messages. Questions directed at children texts such as “What does that say?” or “Read that to me!” are not neutral requests for information, but instead frame the child's text as writing and position the child as a writer (Rowe, 2008b).…”
Section: Theoretical Framementioning
confidence: 99%
“…Micro-analyses of adult-child writing interactions identified two important contexts for adult writing supports (Rowe, 1989(Rowe, , 1994. First, when the researcher served as an audience for the children's composing, she engaged in extensive conversations about their work, foregrounding children's texts as the visual, gestural, and conversational targets of joint attention (Rowe, 2019). Adult supports also included some direct teaching that provided information or explanations of print processes in the context of the child's writing (Rowe, 2008b).…”
Section: Teacher Supports For Writing In Open-ended Meaningful Tasksmentioning
confidence: 99%
“…We distinguish the sort of writing we are referring to from the range of writing young children are asked to do. We envision multimodal composing (e.g., Harste et al, 1984; Rowe, 2019; Wohlwend, 2009), as Hudson's books demonstrate, that includes not just letters and words, but interweaving sign systems such as talk, drawing and bodily movement, all resources that early learners use to create meaning. Relatedly, since the physical products of young children's meaning making through writing are sometimes not yet representational, we consider children's presence, along with their narration and engagement of their bodies, as inseparable from what is on the paper and necessary to understand their compositions.…”
Section: What We Mean By “Writing”mentioning
confidence: 99%
“…Two other studies explored aspects of coaching: Correnti et al (2021) evaluate the impact of online content-focused coaching on dialogic text discussions while Robertson et al (2020) draw on a meta-synthesis of studies of literacy coaching to identify obstacles to and enhancers of co-construction. Rowe (2019) emphasises that child/teacher interactions are multimodal through her analysis of the role of gesture when children are writing with adults.…”
Section: Literacy As Social (10 Articles)mentioning
confidence: 99%